Juridical Review of the Use of Artificial Intelligence in Education: Data Protection, Copyright, and Legal Responsibility Issues - Anggie Sinthiya, Ida Ayu Putu (YHMM PUBLISHING, 2024)
The development of artificial intelligence technology has brought significant transformations in the education sector, ranging from learning personalization, administrative automation, to data-based evaluation systems. However, the implementation of Artificial Intelligence (AI) in education raises various juridical issues, especially related to personal data protection, content copyright, and legal responsibility in the event of losses due to the use of Artificial Intelligence (AI). This article aims to analyze the legal framework that prevails in Indonesia in regulating the use of Artificial Intelligence (AI) in the field of education, focusing on three main issues: data protection, copyright, and legal responsibility. The research method used is normative juridical research with legislative, conceptual, and comparative approaches. The results of the study show that existing regulations, such as Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), the Copyright Law, and the principle of civil liability, can be used as a legal basis to regulate Artificial Intelligence (AI) in education, although more specific regulations are still needed through derivative regulations and Artificial Intelligence ethics guidelines (AI). Thus, the urgency of establishing comprehensive regulations regarding Artificial Intelligence (AI) in education is an urgent need in Indonesia.